The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1038/sj.mp.4001647
|View full text |Cite
|
Sign up to set email alerts
|

Supraphysiological doses of levothyroxine alter regional cerebral metabolism and improve mood in bipolar depression

Abstract: Supplementation of standard treatment with high-dose levothyroxine (L-T 4 ) is a novel approach for treatment-refractory bipolar disorders. This study tested for effects on brain function associated with mood alterations in bipolar depressed patients receiving high-dose L-T 4 treatment adjunctive to ongoing medication (antidepressants and mood stabilizers). Regional activity and whole-brain analyses were assessed with positron emission tomography and [ 18 F]fluorodeoxyglucose in 10 euthyroid depressed women wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
96
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(104 citation statements)
references
References 58 publications
5
96
1
2
Order By: Relevance
“…2,68 TH treatment is also beneficial in bipolar disorders resistant to other forms of treatment. 69,70 Concerning cognitive functioning, there was no difference among the experimental groups in the long-term object recognition memory. A recent study 71 found that treatment with the antimitotic agent methylazoxymethanol acetate reduces neurogenesis in the hippocampus up to 65% and prevents the long-term memory improvement induced by environmental enrichment, as measured in this object recognition task.…”
Section: Discussionmentioning
confidence: 87%
“…2,68 TH treatment is also beneficial in bipolar disorders resistant to other forms of treatment. 69,70 Concerning cognitive functioning, there was no difference among the experimental groups in the long-term object recognition memory. A recent study 71 found that treatment with the antimitotic agent methylazoxymethanol acetate reduces neurogenesis in the hippocampus up to 65% and prevents the long-term memory improvement induced by environmental enrichment, as measured in this object recognition task.…”
Section: Discussionmentioning
confidence: 87%
“…The functional relevance of this structure in mood disorders has been underlined by different lines of evidence, including deep brain stimulation 9 and pharmacological treatment. 10 Furthermore, a pathmodelling meta-analysis of cerebral blood flow in depressive patients 11 has demonstrated that different effective connectivity patterns between the SC and the amygdalo-hippocampal (AH) complex distinguished treatment responders from nonresponders.…”
Section: Introductionmentioning
confidence: 99%
“…Direct clinical evidence for hippocampal pathology in bipolar illness stems from post-mortem histological analysis, [6][7][8][9] volumetric magnetic resonance imaging 10 and [(18)F]fluorodeoxyglucose-positron emission tomography. 11 Recently, magnetic resonance spectroscopy (MRS) has also provided evidence for hippocampal neurometabolite alterations in bipolar disorder. [12][13][14] After 50 years of clinical use, lithium salts have remained the most effective and widely used longterm preventive treatment for bipolar disorder to date.…”
Section: Introductionmentioning
confidence: 99%